Multicomponent Gas-Solid Reactions Kinetic Modelling Of NiOFe2O3 Reduction In Natural GAS - Alias, Nur Syahida (Universiti Sains Malaysia, 2018)
A multicomponent gas-solid reaction is one of the complex reaction that involved the two type of solid reactants with the reducing agent in the form of gas. The reduction of multi-element metal oxide requires high temperature of reduction. Thus, it is so important to discover the best solution in lowering the production cost. Therefore, by using methane as the reducing agent, the cost is reduced because of the price for methane is lower than the other reducing agents. In this study, the reduction of NiO/Fe2O3 by using methane is performed experimentally by using the Design of Experiment(DOE) in variation of parameters. The parameters studied are the reduction time (1hour to 3hours), reduction temperature (800'C to 1000'C) and the molar ratio of NiO to Fe2O3(0.5 to 1.5). Shrinking core model for the isothermal and non-isothermal condition is developed by using MATLAB programming. Based on the shrinking core model, the kinetic modelling of reduction process can be conducted in order to determine the extent of reduction and reaction rate for each condition. The predicted result and the experimental result measured is compared. Based on the DOE analysis, the reduction temperature is the most significant parameter which affect the reduction of oxide. SEM and EDX is used to determine whether the reduction is effective or not. Based on the result, the sample with 0.5 molar ratio of NiO to Fe2O3 which is reduced at 1000oC for 3 hours reduction time shows the highest extent of reduction. From the shrinking core model, the predicted extent of reduction for isothermal shows large different to the experimental result as compare to the non-isothermal condition.